Remapping the Rhetorical Situation in Networked Culture - Pokharel, Ramesh (Cambridge Scholars Publisher, 2021)
With the advent of new media and technology, the notion of the rhetorical situation has changed, and there is now the exigence of a new theory of the rhetorical situation that better incorporates such new notions. By bringing together critical theory of technology and theory of critical geography, along with rhetoric and language theory, this book proposes a new theory on the rhetorical situation that has more explanatory power, and accounts for, frames, critiques, and analyses the fundamental assumptions and beliefs on the rhetorical situation. This theory conceives the constituents of the rh.